Non-Obstructive Linear Intestinal Foreign Body In A Feline – Case Report - Peruzzo , Leandro; Rigon, Vitória; Libardoni, Roberta do Nascimento; Tanabe, Camile Missae; Tonioli, Julia (Seven Editora, 2023)
A foreign body is something ingested by the animal that cannot be digested causing an unstrangled and incomplete mechanical obstruction in the gastrointestinal tract. In cats, linear foreign bodies are the most common, being pieces of string, string, wires, clothing or dental floss. Most clinical signs include vomiting, anorexia, depression and abdominal pain, and there may not be vomiting if the foreign body is located in the gastric fundus and does not obstruct the pylorus (FOSSUM, 2021). Oral or anal traction is contraindicated as it can tear the gastrointestinal tract and cause ruptures. The aim of this study is to report the treatment approach adopted in a feline with a non-obstructive linear intestinal foreign body. DOI: https://doi.org/10.56238/methofocusinterv1-095